Learning expectations, challenges, and strategies of university students on English-medium instruction - Syariful Muttaqin; Hsueh-Hua Chuang (Journal on English as a Foreign Language, 2022)
Despite its wide application at tertiary education, English-medium instruction (EMI) poses complexities in practices. This study investigated EMI students’ expectations, challenges, and coping strategies based on prior learning and language backgrounds and explored EMI policy implementation at a university in Indonesia. The qualitative data were obtained from open-ended questionnaires, a focus group interview, with participants selected using purposive sampling for maximum variation, and EMI policy documents from a faculty of economics and business at an Indonesian university. The data were analyzed inductively by looking at the recurring themes and were used for triangulation. The students’ different backgrounds: mainstream, mainstream with English courses, and bilingual or international classes brought some differences in their EMI learning. Students had high language, career, academic, relational, and intercultural expectations. Those from mainstream classes faced considerably more challenges compared to those from the other groups with stronger English backgrounds, regarding inadequate English proficiency, unfamiliarity with academic and disciplinary terms, and struggling in following lectures. The students’ learning strategies relied on cognitive and rote learning with the assistance of digital technology. Finally, a gap was observed between meso and micro policy and practice. More institutional supports thus were recommended for better achieving the EMI program vision.